Ortodoxia y Heterodoxia en el estudio de la Escultura Románica Española: Estado de la cuestión - Valdez del Alamo, Elizabeth (Anuario del Departamento de Historia y Teoría del Arte, 1998)
A review of the scholarship of Spanish Romanesque sculpture ca. 1070-1200. Methodological problems covered include the definition of "Romanesque", the local and imported sources for architectural sculpture in the Iberian Península, the impact of patronage and of the pilgrimage to Santiago de Compostela, the disjunction of the documents and monuments, and the widely varying chronologies for the Peninsula’s most significant sites. Monuments discussed include León, Jaca, Frómista, Compostela, Silos, Soria, Pamplona, San Juan de la Peña, and Zaragoza. Iconographic studies and methods appropriate for the special circumstances of medieval Spain are also considered.